Rancang Bangun Sistem Pendukung Keputusan Tanaman Pangan Kelompok Tani Menggunakan Metode Simple Additive Weighting - Gilang Pramudia Fabriandi; Anisya Sonita; Khairullah Khairullah; A.R Walad Mahfuzi (UNIVED Press, 2025)
Abstract— Agriculture is a very important sector for the Indonesian economy, where the majority of the population depends on this sector for their livelihood. Farmer groups play a key role in increasing food production and farmer welfare. However, selecting the right type of food crop is often a challenge for farmers because it involves various criteria and factors. Therefore, a decision support system is needed that can help farmer groups in determining optimal food crop choices. This research aims to design and build a decision support system (DSS) for farmer groups using the Simple Additive Weighting (SAW) method. The SAW method was chosen because of its ease in combining various criteria and factors in decision making. It is hoped that the system being built can help farmer groups increase the efficiency and effectiveness of decision making regarding food crop selection. The research results show that the use of the SAW method in SPK is able to provide accurate and reliable recommendations, so that it can support increased productivity and welfare of farmers.